Value-based adoption of MDS:an empirical investigation - ZHOU Yi1; MENG Wei-dong1; DU Hui-ying2; WU Ping-yao2 (Tongxin xuebao)
The influence factors of customers’ behavioral intention,and constructs the regression model for the influence factors of customers behavioral intention of mobile data services（VAMDS） was analyzed.China mobile users of ease-own,GoTone and M-zone are chosen as our random surveys in Beijing,Nanjing and Chongqing.That the top three most important factors of customers behavioral intention of MDS are price,usefulness and social influence,and the security for customers’ behavioral intention validated by overseas scholars isn’t supported in the main MDS in China now.